The Utilization of Seconhand into Chemical Props with a Service Learning Approach - Nur Azzanizawaty Binti Yahya; Ratna Kumala Dewi (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
Chemistry learning is currently related to contextual or learning associated with everyday life. Many secondhand can be used in the surrounding environment as learning resources. Learning resources that can be made from secondhand is chemical property. This service focuses on high school /MA chemistry teachers in Tulungagung. This service aims to increase chemistry teachers' knowledge about the importance of using secondhand as chemical property. The method used Service Learning. The service-learning methods are preparation, action, reflection, assessment and evaluation. The results of chemical property that can be made with secondhand are periodic systems of elements, hydrocarbons, electrolytes, colloids, pop-up books, molecular shapes, acids and bases, Thomson atomic models, Rutherford atomic models, monopoly reaction rates, chemical bonds, reaction rate madding, electron configuration magic box, and redox light. Based on the results and discussion, it can be concluded that chemical property can be made from secondhand with a Service Learning approach to increase creative and innovative learning for teachers and students high school/MA in Tulungagung.